2022
DOI: 10.3390/children9050703
|View full text |Cite
|
Sign up to set email alerts
|

Windswept Deformity a Disease or a Symptom? A Systematic Review on the Aetiologies and Hypotheses of Simultaneous Genu Valgum and Varum in Children

Abstract: Objective: The objective of this study is to create an overview of the possible aetiologies of windswept deformity and to emphasize the points of attention when presented with a case. Methods: A systematic search according to the PRISMA statement was conducted using PubMed, African Journals Online, Cochrane, Embase, Google Scholar, and Web of Science. Articles investigating the aetiology of windswept deformity at the knee in children, and articles with windswept deformity as an ancillary finding were included.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…In late childhood and adolescence, when deformities such as severe varus, valgus, or windswept lower leg deformities become more pronounced, treatment often involves surgical interventions [4,14]. Surgical interventions like guided growth surgery offer a less invasive option for correcting coronal plane deformities, allowing patients a quicker return to normal activities [3,4,[6][7][8]10].…”
Section: Discussionmentioning
confidence: 99%
“…In late childhood and adolescence, when deformities such as severe varus, valgus, or windswept lower leg deformities become more pronounced, treatment often involves surgical interventions [4,14]. Surgical interventions like guided growth surgery offer a less invasive option for correcting coronal plane deformities, allowing patients a quicker return to normal activities [3,4,[6][7][8]10].…”
Section: Discussionmentioning
confidence: 99%
“…However, in ambulatory children, this deformity mainly affects the knees and is also referred to as varo-valga knees. A recent systematic review revealed that there were fewer than 200 documented non-neurologic pediatric cases, typically attributed to causes such as rickets, metabolic disorders, genetic skeletal dysplasias, or trauma [8]. Nevertheless, the etiology remains unknown in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we present a case of "windswept deformity" of the knees in a 15-yearold boy. "Windswept deformity" is defined as the phenotypical presentation of a varus and valgus deformity with variable localization and underlying pathologies [8]. A recent systematic review identified 184 cases of children with "windswept deformity" reported in the literature in patients affected by rickets or skeletal dysplasias in the majority of cases [8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations